1. ANALISIS SENYAWA BENZOAT PADA KECAP MANIS PRODUKSI LOKAL KOTA MANADO - Taib, Muh. Zaid (PHARMACON, 2014)
Soy sauce is one of the food additives commonly added to food . The purpose of this study is to determine the levels of benzoic acid compounds contained in soy sauce Manado city product. Samples were taken from four brands of soy sauce on the four markets in the city of Manado . Identification of the samples was done by FeCl3.Analysis of benzoic acid content using UV-Vis spectrophotometry methode with wavelength of 280 nm. The results showed that four samples of soy sauce using as preservative benzoic acid about 18,59 mg/kg, 20,32 mg/kg, 19,97 mg/kg dan 21,46 mg/kg. Benzoic acid in the sample does not exceed the predetermined threshold in PERMENKES RI No.Â  722/Menkes/Per/IX/88. Â  Key words : Benzoic, soy sauce, UV - Vis spectrophotometry, Manado